2020
DOI: 10.1155/2020/8393504
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Sinapic Acid on Dextran Sodium Sulfate- (DSS-) Induced Ulcerative Colitis in Kunming (KM) Mice

Abstract: Ulcerative colitis is a chronic gastrointestinal disease characterized by intestinal inflammation and serious mucosal damage. As a naturally hydroxycinnamic acid, sinapic acid (SA) has antioxidant, anticancer, and neuroprotective activities. We investigated the anticolitic effect and potential mechanisms of SA in DSS-induced colitis in Kunming (KM) mice. SA treatment significantly reduced body weight loss, colon shortening, and intestinal wall thickening in colitis mice. SA treatment also significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Mediators of Inflammation structure. Recent studies have suggested that SA has antiinflammatory effects on intestinal inflammation and can regulate the intestinal microbiota and improve the redox state [25,29,30]. In the current investigation, we attempted to appraise the effects of SA on intestinal inflammation and permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediators of Inflammation structure. Recent studies have suggested that SA has antiinflammatory effects on intestinal inflammation and can regulate the intestinal microbiota and improve the redox state [25,29,30]. In the current investigation, we attempted to appraise the effects of SA on intestinal inflammation and permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived phenolic compounds are a type of organic acid that contains either a benzoic or cinnamic acid skeleton with phenol as the basic framework and a relatively simple structure. Recent studies have suggested that SA has anti-inflammatory effects on intestinal inflammation and can regulate the intestinal microbiota and improve the redox state [ 25 , 29 , 30 ]. In the current investigation, we attempted to appraise the effects of SA on intestinal inflammation and permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Sinapic acid is a hydroxycinnamic acid widely found in many foodstuffs, such as vegetables, spices, citrus, berry fruits, cereals, oilseed crops, wine, and vinegar. Sinapic acid has shown antioxidant and anti-inflammatory properties [ 134 ], as well as a modulating activity against the NLRP3 inflammasome complex in mouse models with chemically induced colitis [ 57 ]. The monitoring of NLRP3 inflammasome protein levels in the inflamed colon tissue of Kunming mice (colitis model), by Western blot analysis, after sinapic acid treatment for 7 days, have shown a reduction in the amounts of NLRP3, ASC, IL-1β, and caspase-1 proteins.…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…Next, in vivo and in vitro experiments verified that silencing exosomal miR-181a aggravated inflammation in colon tissue and increased inflammatory factor levels and apoptosis. It has been reported that MPO might serve as an important diagnostic and prognostic tool in assessing UC status ( 30 ). The MPO activity in colon tissue was downregulated in the MSC-con group compared with that in the DSS group.…”
Section: Discussionmentioning
confidence: 99%